SEXUAL LIFE AS TOLD BY SEMINARIANS: Can Seminary Formation Prevent Clergy Sexual Abuse? - Riyanto, FX. Eko Armada (Asian Horizons, 2020)
This article is based on my research of the sexual life as told by seminarians. The aim of research is to find out more precisely opinions and stories of their sexual experience. My assumption is that the crisis of the Catholic Church with regard to sexual abuse committed by the clergy has to be taken seriously since the beginning of the life-processing of the sexual life of the seminarians in the initial formation. The methodology of the research is an open questionnaire with phenomenological approach which gives more space to the subjects to share personal stories. From a hundred respondents, ninety-eight of them wrote down their experiences in a closed letter. The result is that many of them have “uncomfortable experiences” of sexuality or even suffer sort of sexual violence connected with the family background and friends. Some serious traumatic experiences could cause them to be a “wounded person” from the standpoint of sexuality. They need really a proper assistance in formation program.